The Nature and Scope of Racial Profiling in Routine Traffic Stops - Boykin, Margie (My University, 2020)
The purpose of this research is to examine whether law enforcement officers are racially profiling minorities during traffic stops. In the Criminal Justice System, racial profiling against minorities has been a serious issue. The most powerful character of racial divide in the United States is because young Black males seem to be targeted by law enforcement officers. By no means is the unequal treatment of racial minorities by police a new concept. The formal discussion over racial profiling has a focus on three main questions, does racial profiling really occur? If it does, is racial profiling being used, and is profiling a legitimate implement of law enforcement? The reason for this research is to determine whether race is a sufficiently great factor in the probability of being involved in a traffic stop in regards to race. The research will focus on the different issues of the nature and scope of racial profiling in routine traffic stops. It will discuss whether race of the individuals stopped or the crime itself is the reason why they are being stopped. Research has verified that people of color are more often to get stopped by law enforcement officers. Research has shown that race is an act predictor of attitudes toward police. I have chosen this topic because there have been numerous cases where law enforcement officers have stopped and harassed innocent minorities during a traffic stop. Also my son, a Black American has been racial profiled because of his hair style even though he was a student of University of West Georgia and has never been in trouble with law enforcement. Research can establish the need for profiling based assessment at the community level. Keywords: Racial Profiling, Racism, Discrimination, Criminal Justice
Chapter I: INTRODUCTION 1 -- Statement of the Problem 3 -- Chapter II: REVIEW OF LITERATURE 5 -- What is the impact of racial profiling by the police decision to stop an individual? 7 -- What are individual perceptions of citizens stopped by police? 8 -- Does racial profiling have negative effects on the characteristic of those targeted by the police? 9 -- How are racial disparities in traffic stops associated with characteristics of police departments? 10 -- Why and how does police officers make the decision to stop an individual for a traffic stop? 11 -- What are law enforcement factor for stopping citizens during a traffic stop; race or behavior? 13 -- Does race has a determining factor in action after the stop? 14 -- Chapter III: METHODOLOGY 16 -- Overview 16 -- Data Source 19 -- Summary 22 -- Chapter IV: RESULTS 24 -- Chapter V: CONCLUSION 30 -- REFERENCES 35 -- APPENDIX A: Reason for Traffic Violations and (IRBA) Exemption 38.
Keywords: Academic theses; Criminal justice, Administration of; Racial profiling in law enforcement; Racism; Race discrimination